A deliberação CEE/SP nº 111/2012 e a perspectiva da autonomia universitária: uma leitura a partir do Departamento de Educação da UNESP/Rio Preto - Sena, Marcos Danillo Lopes de (2021)
In this master's thesis, we conducted a study about the role of the State Council of Education in the organization, administration and regulation of public universities in the state of São Paulo. As a research objective, we analyze the process of external regulation exercised by CEE/SP, focusing on the case of the Department of Education of the São José do Rio Preto "Júlio de Mesquita Filho" State University of São Paulo (UNESP) through the implementation of CEE Deliberation No. 111/2012. The Deliberation CEE nº 111/2012 was one of the milestones in the clashes of the relationship between the CEE/SP and the public universities in the state, since it proposed reformulations for the undergraduate courses and established changes in the Curricular Matrices, which is a setback in teacher training policies for basic education by hurting university autonomy. A brief journey through the history of university autonomy, which, among other researchers, has Marilena Chauí as a scholar. The author's writings regarding university autonomy were the gateway to the theoretical understanding of this research. Besides Chauí (2018), we used as reference to understand the concept of autonomy authors such as: Cury (1991); Sobrinho (1992); Mancebo (1999); Mendonça (2000); Kinzo (2001); Cunha (2003); Deligdisch (2004); Fávero (2004); Trindade (2004); Lima (2005), among others. The methodological path used is bibliographic, documental and semi-structured interviews, being a descriptive qualitative approach. In the documental analysis, the laws of creation of the São Paulo State Board of Education are analyzed, as well as the normative devices elaborated by this body, as in the case of Deliberation CEE nº 111/2012. The documentary research also included institutional documents from the creation of UNESP, the university's internal regulations, and public domain documents found on the university's official website. In conducting the interviews, it was possible to see that the Council maintains an energetic relationship with the universities, and in the case of the implementation of 111/2012, it acted in an arbitrary manner. It is important to remember that the CEE/SP acts (or should) as a guiding body, regulator, and accreditor of the basic education schools of the state network, of the private network, and of the courses of public higher education institutions in the state. In the analysis of the interviews and documents, it was found that Deliberation CEE nº 111/2012 proposes modification in the formative structure of courses that emphasize a greater emphasis on practical training. University autonomy is an ongoing process; it is a permanent struggle of resistance against the neoliberal agenda model. The work proposes to continue provoking the debate and reflections about the limits of the CEE and the resistance of universities to maintain their guarantees of didactic and scientific autonomy.